APPLICATION OF CUSTOMER LAPTOP LOAN INSTALLMENTS BASED ON THE EFFECTIVE AND FIXED INTEREST RATE METHOD - Amika Sapan; Yohanis Tasik Allo (Bajang Institute, 2022)
Financial institutions (finance) are currently growing rapidly by providing various kinds of attractive credit facility promotions to their customers. The public can take advantage of this financing service, if the administrative requirements are complete. Credit promotions are given to customers in the form of a list of installments with varying interest according to the desired amount of credit for each installment period. This study aims to determine the application of mathematical concepts by using the annuity interest rate system and sliding rate as well as flat interest rates. The data analysis model used in this study is an exploratory method and the data collection is secondary data by taking several price list brochures of six ( 6) brands of laptops from various types and three (3) financial institutions (finance). The data obtained are down payment (DP), interest rate (i), insurance costs, administrative costs and credit installment period. After the data is obtained, then the analysis and calculation is carried out with the following steps: (1) Performing the calculation of flat interest, annuity interest and sliding rate interest; (2) Calculation of monthly installments on annuity and sliding rate. Based on the results of data processing , it is found that the greater the loan value, the smaller the interest rate charged to consumers and the longer the payment period, the smaller the interest rate charged to consumers. The results of this study, concluded that The payment system that is more profitable for the finance party is the flat interest rate system, while the system that is best used for the customer is the effective interest rate system, namely the sliding rate system . This system, gives customer interest relief decreased. However, if the customer wants to pay off early, the sliding rate and flat interest rate system is more profitable for the customer. While the annuity interest rate uses declining interest, the amount of interest earned is greater than the sliding rate interest The principal installments are getting bigger and bigger